2018
DOI: 10.1021/acs.accounts.8b00321
|View full text |Cite
|
Sign up to set email alerts
|

Toward Understanding the Chemistry and Biology of 1-Deoxy-d-xylulose 5-Phosphate (DXP) Synthase: A Unique Antimicrobial Target at the Heart of Bacterial Metabolism

Abstract: Antibiotics are the cornerstone of modern healthcare. The 20th century discovery of sulfonamides and β-lactam antibiotics altered human society immensely. Simple bacterial infections were no longer a leading cause of morbidity and mortality, and antibiotic prophylaxis greatly reduced the risk of infection from surgery. The current healthcare system requires effective antibiotics to function. However, antibiotic-resistant infections are becoming increasingly prevalent, threatening the emergence of a postantibio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(58 citation statements)
references
References 49 publications
2
56
0
Order By: Relevance
“…This thiamin diphosphate (ThDP)-dependent enzyme catalyzes the decarboxylative condensation of pyruvate and d-glyceraldehyde 3-phosphate (d-GAP) to form 1-deoxy-d-xylulose 5-phosphate. This metabolite is involved in three separate essential pathways for central bacterial metabolism: ThDP synthesis, pyridoxal phosphate (PLP) synthesis, and the methylerythritol phosphate (MEP) pathway for isoprenoid synthesis [35].…”
Section: Secondary Metabolite Synthesismentioning
confidence: 99%
“…This thiamin diphosphate (ThDP)-dependent enzyme catalyzes the decarboxylative condensation of pyruvate and d-glyceraldehyde 3-phosphate (d-GAP) to form 1-deoxy-d-xylulose 5-phosphate. This metabolite is involved in three separate essential pathways for central bacterial metabolism: ThDP synthesis, pyridoxal phosphate (PLP) synthesis, and the methylerythritol phosphate (MEP) pathway for isoprenoid synthesis [35].…”
Section: Secondary Metabolite Synthesismentioning
confidence: 99%
“…To this end, studies of DXP synthase have discovered unique structural and mechanistic features that set it apart from others in the ThDP enzyme family, enabling the design of potent, selective inhibitors. [5][6][7][8][9] Early structural studies revealed a unique domain arrangement and novel positioning of large active sites on DXP synthase, distinct from transketolase (TK) and the E1 component of the Escherichia coli pyruvate dehydrogenase complex (E1-PDH). 10,11 In addition, mechanistic studies have demonstrated a unique mechanism for DXP synthase in which the first enzyme-bound intermediate, C2α-lactylThDP [LThDP ( Figure 1)], is stabilized in the absence of an acceptor substrate.…”
Section: Graphical Abstractmentioning
confidence: 99%
“… 2 , 13 , 14 These structural and mechanistic features of DXPS have guided the development of inhibitors that display selective inhibition of DXPS over related ThDP enzymes. 7 , 8 , 21 23 …”
mentioning
confidence: 99%